2016
DOI: 10.1136/annrheumdis-2015-208914
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, single-blind, single-dose, three-arm, parallel-group study in healthy subjects to demonstrate pharmacokinetic equivalence of ABP 501 and adalimumab

Abstract: ObjectiveTo demonstrate pharmacokinetic (PK) similarity of biosimilar candidate ABP 501 relative to adalimumab reference product from the USA and European Union (EU) and evaluate safety, tolerability and immunogenicity of ABP 501.MethodsRandomised, single-blind, single-dose, three-arm, parallel-group study; healthy subjects were randomised to receive ABP 501 (n=67), adalimumab (USA) (n=69) or adalimumab (EU) (n=67) 40 mg subcutaneously. Primary end points were area under the serum concentration-time curve from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
67
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 19 publications
16
67
1
1
Order By: Relevance
“…In this study, the percentages of subjects over time with binding ADA formation and nADA formation were similar among all study arms. The results were also consistent with other recent studies evaluating biosimilars of Humira . In the M923 study, the proportion of subjects with a confirmed ADA response, the rate of ADA seroconversion over time, and the occurrence of nADAs were in line with that reported by Kaur et al .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the percentages of subjects over time with binding ADA formation and nADA formation were similar among all study arms. The results were also consistent with other recent studies evaluating biosimilars of Humira . In the M923 study, the proportion of subjects with a confirmed ADA response, the rate of ADA seroconversion over time, and the occurrence of nADAs were in line with that reported by Kaur et al .…”
Section: Discussionsupporting
confidence: 92%
“…The results were also consistent with other recent studies evaluating biosimilars of Humira . In the M923 study, the proportion of subjects with a confirmed ADA response, the rate of ADA seroconversion over time, and the occurrence of nADAs were in line with that reported by Kaur et al . A lower ADA response (44%) has been reported with LBAL, a Humira biosimilar that is currently in development .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is important to understand because if such sensitive assays are used during biosimilar development it may lead to the perception that the ADAs are much higher than originally seen with the reference products. However, in comparative biosimilar studies using more sensitive methods, serum levels in patients receiving reference product should be similar to those in patients receiving the proposed biosimilar . Increased sensitivity may also lead to potentially false positives; including patients who are naive to drug and have ADAs prior to exposure.…”
Section: Development Of Biosimilars: Analytical Preclinical and Clinmentioning
confidence: 99%